Selenium level correlates negatively with antibodies but positively with thyroid function in children with down syndrome: an Indonesian study - Hisbiyah, Yuni; Endaryanto, Anang; Setyoboedi, Bagus; Rochmah, Nur; Faizi, Muhammad; Fedora, Katherine (Frontiers in Endocrinology, 2023)
Abstract Background: Children with Down syndrome (DS) are prone to developing autoimmune thyroid disease (AITD). Previous studies found lower selenium (Se) levels in children with AITD. Glutathione peroxidase-3 (GPx3) and selenoprotein-P (SePP) are widely used to measure Se levels. DS children tend to have lower Se levels, the main contributor to hypothyroidism in this population. This study aimed to analyze the Se’s role in AITD in Indonesian children with DS. Methods: This cross-sectional study was conducted between February 2021-June 2022 at the Pediatric Outpatient Clinic of Dr Soetomo Hospital. DS children aged 1 month to 18 years were enrolled using consecutive sampling. Thyroid-stimulating hormone, free thyroxine, thyroid peroxidase (TPO-Ab) and thyroglobulin (Tg-Ab) autoantibody, GPx3, and SePP levels were measured in plasma samples using enzyme-linked immunosorbent assays. Statistical analyses used Chi-square, Mann–Whitney, and Spearman’s rank correlation (rs). All results with p<0.05 were considered statistically significant. Results: Among 62 children with DS, SePP and GPx3 levels were significantly lower in those with AITD than those without AITD (p=0.013 and p=0.018, respectively). SePP and GPx3 levels correlated significantly with lower TPO-Ab (rs=−0.439 with p=1×10-5 and rs=−0.396 with p=0.001, respectively) and Tg-Ab (rs=−0.474 with p=1×10-5 and rs=−0.410 with p=0.001, respectively) levels. SePP levels correlated significantly with lower thyroid dysfunction incidence (rs=-0.252, p=0.048) in the AITD group. Conclusions: Se levels correlated significantly with lower autoimmune thyroid markers in DS children. Our findings recommend increasing Se levels through Se-containing foods to reduce the risks of AITD and thyroid dysfunction in DS children with AITD.